Effective Consumption and Non-Keynesian Effects of Fiscal Policy - Kristian Jönsson (Lund University, School of Economics and Management, Department of Economics, 2004)
In this paper, we elaborate on the notion of effective consumption and its role in determining the outcome of fiscal changes. More specifically, we investigate whether government consumption, by acting either as a complement or a substitute to private consumption, can help explain the non-Keynesian effects of fiscal policy that have been previously documented. We let the periods, where government consumption has acted as a complement or a substitute to private consumption, constitute different regimes. By using econometric methodologies that allow the these regimes to be determined both exogenously and endogenously, we find that the notion of effective consumption can assist in understanding the non-Keynesian effects of fiscal policy that have been documented in Denmark, Ireland and Sweden.
Keywords: E21; E62; 330; Private Consumption; Fiscal Policy; Government Consumption